Effects of a computer-based enrichment programme on the development of analytical and creative abilities in gifted students. Issue 9 (21st October 2022) - Gubbels, Joyce; Segers, Eliane; Verhoeven, Ludo
Abstract: Enrichment programmes are designed to offer gifted students experiences that are not covered in the regular curriculum We used a pre-test–post-test control group design to examine the effects of a computer-based enrichment programme on the development of analytical and creative abilities in 26 gifted children in an experimental group (15 boys, mean age = 10 years and 3 months) and compared this to 20 equally gifted children in a control group (8 boys, mean age = 10 years and 4 months). Students were identified as being analytically gifted, creatively gifted, or analytically-creatively gifted. In general, results showed increasing levels of analytical ability and stable levels of creative ability. In addition, hierarchical regression analyses showed a positive effect of the enrichment programme on the development of analytical abilities in children with relatively low starting levels of analytical ability (i.e. the creatively gifted students). To conclude, results suggest that rather than analytically gifted children, children with creative talents gained most advantage from participating in the computer-based enrichment programme.